The Influence of Think, Predict, Read, and Connect Strategy Towards Students’ Reading Comprehension - Amalia Lintang Amandari; Eva Nurchurifiani; Purna Wiratno (IJLHE: International Journal of Language, Humanities, and Education, 2023)
The research aimed to know the influence of Think, Predict, Read, and Connect strategy on students’ reading comprehension. This strategy helped the students comprehend main idea, supporting idea, inference, reference and vocabularies of the text. In this research the writer used quantitative method and categorized the research as quasi experimental method. The sample was taken by using Cluster Random Sampling technique. There were two classes for the sample. X PM 1 was an experimental class consisted of 35 students and X PM 2 was a control class consisted of 34 students. Based on the data analysis and testing of hypotheses, it showed that the average score of students who were taught through Think, Predict, Read, and Connect (TPRC) strategy was higher than which was taught through direct instruction. It was got 75.24 > 63.97 and in the end of result, it showed that was higher than . In the calculation of two averages score, it was obtained 3.99 > 2.00 < 2.66 and in the calculation of the difference of two averages score, it was obtained 3.99 > 1.67 < 2.39. Therefore, it can be concluded that there was a significance influence of using Think, Predict, Read, and Connect strategy towards students’ reading comprehension at the tenth grade of SMK Negeri 4 Bandar Lampung in 2022/2023.